Analysing consumer-brand engagement through appreciative listening on social network platforms - Pina, L. S.; Loureiro, S. M. C.; Rita, P.; Sarmento, E. M.; Bilro, R. G.; Guerreiro, J. (Journal of Promotion Management, 2019)
The evolution of technology changed the external environment surrounding businesses creating a plethora of new opportunities and challenges. Particularly, social network platforms became attractive to companies due to their interactive nature as they increase consumers’ and brand opportunities for developing long-term relationships and engagement. In this sense, the main goal of this article is to understand whether appreciative listening can contribute to the improvement of consumer-brand engagement using these platforms. We develop two studies based on Starbuck’s facebook page whereby findings from study one are used as inputs to study two. Results demonstrate that appreciative listening can actually improve consumer-brand engagement.